ACTION PLANS AGAINST WOMEN'S INVISIBILITY HOME WORKER (PUTTING OUT SYSTEM) - Handayani, Diah; Taufiq, Ahmad (UNIVERSITAS PAKUAN, 2020)
The purpose of this study is to know the profile of women of home workers (Putting Out System/POS) in Kediri Regency, covering aspects of the establishment, categorisation, social security and the recognition of Putting Out System in Kediri Regency. The type of research developed in this study is a qualitative approach. According to Narbuko (2008), qualitative methods refer to research strategies, such as observation, in-depth interviews, focus group discussions and document studies. The results showed that home workers were scattered in several areas in several sub-districts. Although no data indicates clearly but their existence is very significant. In carrying out its work, women of home workers face some of the following problems:(1) There is no written agreement about the terms and conditions, (2) Low wages; based on the product unilaterally determined by the employer. (3) No labor social protection. Even if they have health insurance, it is because they are in the status of poor households so it is entitled to the beneficiaries of government-managed healthcare social security (JKN-KIS, JKN-KIS District, JAMKESDA) or have BPJS Mandiri. The inhibitory factors of the change in the access of women of home workers to the collateral of social protection of man power are as follows: logging constraints, regulatory constraints, social and family norms that impede women to participate in mentoring collective pursuits. There are two things that can encourage poor female home workers to access the social protection of labor, which is participation in collective action and the ability to negotiate with employers